Sex-Specific Stress Tolerance in Embryos of Lake Char (Salvelinus umbla) - Nusbaumer, David; Garaud, Laura; Ançay, Laurie; Wedekind, Claus (Frontiers in Ecology and Evolution, 2021)
Salmonid fish have become important models in evolution and ecology, but possible effects of embryo or larval sex are mostly ignored, probably because morphological gonad formation starts only months after hatching and sexual maturation years later. However, recent gene expression studies and first observations in domestic strains suggest that sex-specific life histories could already start at an embryonic stage. Here we test this hypothesis in embryos and larvae of lake char (Salvelinus umbla). We sampled wild char and used their gametes to produce embryos of 40 different families. Embryos were raised singly in a stress or a non-stress environment until a late larval stage (stress was induced by allowing remainders of ovarian fluids to support microbial growth). Genetic markers were then used to sex the fish and reconstruct paternity (N = 1,463, including dead embryos). Primary sex ratio did not differ among families and was about 1:1. Female embryos hatched on average later and showed lower stress tolerance than male embryos. There were significant parental effects on offspring growth and mortality, but the sex differences in embryo performance were not family specific. We conclude that the sexes differ in their life history and susceptibilities to environmental stress already at embryonic stages. Environmental stress during incubation can therefore affect population sex ratio and hence population growth and genetics.